2023
DOI: 10.1039/d2cp05264d
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal vibrational anisotropy and thermal properties of a two-dimensional GeAs semiconductor

Abstract: The anisotropy in the crystal structure plays a striking role in the optical, electrical and thermal properties of the condensed matter. Here, we investigate the in-plane vibrational anisotropy in two-dimensional...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Where C v , V̄ , and τ T are heat capacity under constant volume, averaged acoustic phonon velocity, and the thermal transport relaxation time, respectively. Under the assumed conditions, where C v is 2 k B and V̄ is 5 km s −1 , 4,59 the thermal transport relaxation time can be approximated as the quasi-particle lifetime of the Raman optical phonon τ , . By referring to the FWHM ( Γ ) value in the range of 8–16 cm −1 , τ ranges from 0.33–0.66 ps.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Where C v , V̄ , and τ T are heat capacity under constant volume, averaged acoustic phonon velocity, and the thermal transport relaxation time, respectively. Under the assumed conditions, where C v is 2 k B and V̄ is 5 km s −1 , 4,59 the thermal transport relaxation time can be approximated as the quasi-particle lifetime of the Raman optical phonon τ , . By referring to the FWHM ( Γ ) value in the range of 8–16 cm −1 , τ ranges from 0.33–0.66 ps.…”
Section: Resultsmentioning
confidence: 99%
“…Low-symmetric two-dimensional (2D) layered materials present intriguing in-plane anisotropy. [1][2][3][4] For instance, GaTe, GeSe, GeAs, and black phosphorus have been reported to have significant directional dependence of their photoemission, thermoelectricity, and mobility properties, mainly due to the anisotropic light-matter interactions, such as the electronphoton and electron-phonon couplings. 1,2,[4][5][6][7][8] As a typical binary IV-VI chalcogenide with a rhombohedral (α-phase; or pseudo-cubic) crystal structure at room temperature that is formed by distortion at high-temperature of the cubic phase, 9,10 GeTe (R3m-C 3v space group) has advantages for application in thermal-/opto-electronic devices, e.g., with a maximum thermoelectric figure-of-merit (ZT ) value of ∼0.8 that can be improved up to the currently known 2.7 at 750 K (ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When these elements containing lone electrons are mixed with transition metals, the lone electron is usually a “chemical scissor”, thereby generating a layered or low-dimensional compound, as reported by Takagi et al 12 In this case, they can present more diverse crystal structures and intriguing optical/electrical/magnetic properties than common two-dimensional materials including ferroic semiconductors. 13,14…”
Section: Introductionmentioning
confidence: 99%
“…When these elements containing lone electrons are mixed with transition metals, the lone electron is usually a ''chemical scissor'', thereby generating a layered or low-dimensional compound, as reported by Takagi et al 12 In this case, they can present more diverse crystal structures and intriguing optical/electrical/magnetic properties than common two-dimensional materials including ferroic semiconductors. 13,14 Recently, a Raman study on Fe 2 O(SeO 3 ) 2 (FSO), accompanied by magnetic susceptibility measurements, found that below T N B 105 K it exhibits an antiferromagnetic behavior. 15 However, unlike other saw-tooth chain compounds, this oxoselenite shows a low-dimensional behavior above T N , which cannot be described by the Curie-Weiss law but was interpreted as an indication of the proximity of FSO to a quantum critical point (QCP).…”
Section: Introductionmentioning
confidence: 99%